EFEKTIVITAS PENERAPAN PRICE LIMIT DI BURSA EFEK JAKARTA - Mario Rita; Eduardus Tandelilin (Journal of Indonesian Economy and Business (JIEB), 2007)
Some stock markets have employed price limit to prevent market crash. The question about the effectiveness of price limit has long attracted research interest. Price limit advocates claim that price limits decrease stock return volatility, counter overreaction, and do not interfere with trading activity. Conversely, price limit critics claim that price limits cause higher volatility levels on subsequent days, prevent prices from efficiently reaching their equilibrium level, and interfere with trading due to limitations imposed by price limits. Empirical research does not provide conclusive support for either positions.This study empirically investigates the impact of a wide price limit on volatility, and overreaction, using the data from the Jakarta Stock Exchange, over the years 2000-2005. More specifically this study examines whether daily return volatility for stock-hit price limit are expected to be lower in the post limit hit period than the sample control groups. Beside that, in this study the phenomenon of short-term overreaction are examined.The main difference of this paper with the previous literatures is that this study compares volatility levels before and after price limit implementation on JSX.Firstly, empirical results indicate that volatility after price limit implementation shows highest level than before. Second, the results show that stocks-hit experiences their highest level of volatility on the day when stock-hit reach their limits, and then decreases significantly after the hit. Third, the findings indicate the occurrence of short-term overreaction for the sample of downward stock price movement, but not for the sample of upward stock price movement.